2008
DOI: 10.1002/ijc.23602
|View full text |Cite
|
Sign up to set email alerts
|

Tumor expressed PTHrP facilitates prostate cancer‐induced osteoblastic lesions

Abstract: Expression of parathyroid hormone-related protein (PTHrP) correlates with prostate cancer skeletal progression; however, the impact of prostate cancer-derived PTHrP on the microenvironment and osteoblastic lesions in skeletal metastasis has not been completely elucidated. In this study, PTHrP overexpressing prostate cancer clones were stably established by transfection of full length rat PTHrP cDNA. Expression and secretion of PTHrP were verified by western blotting and IRMA assay. PTHrP overexpressing prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 54 publications
4
75
1
2
Order By: Relevance
“…In Pthrp-ablated animals, primary tumor hyperplasia was considerably delayed, and palpable tumors appeared much later and were smaller and fewer than in control mice. Our observations are in agreement with several clinical studies in which patients with tumors produc- ing high PTHrP levels presented higher rates of metastasis and increased or earlier mortality (40)(41)(42)(43). A recent report reached opposite conclusions, but relied on animal models with a very late-onset oncogenic system (neu based), which is more relevant to tumors arising in older animals (44), and used mice with a heterogeneous genetic background.…”
Section: Discussionsupporting
confidence: 88%
“…In Pthrp-ablated animals, primary tumor hyperplasia was considerably delayed, and palpable tumors appeared much later and were smaller and fewer than in control mice. Our observations are in agreement with several clinical studies in which patients with tumors produc- ing high PTHrP levels presented higher rates of metastasis and increased or earlier mortality (40)(41)(42)(43). A recent report reached opposite conclusions, but relied on animal models with a very late-onset oncogenic system (neu based), which is more relevant to tumors arising in older animals (44), and used mice with a heterogeneous genetic background.…”
Section: Discussionsupporting
confidence: 88%
“…Further experiments are needed to address the role of other factors produced by prostate cancer cells that effect osteoclast formation. For example, it has been demonstrated that PTHrP produced by prostate cancer cells can facilitate osteoclastogenesis and osteoblastogenesis [Li et al, 2007;Liao et al, 2008]. This study demonstrates that functional osteoclasts can be derived from CD11b+ cells derived from human PBMCs.…”
Section: Discussionmentioning
confidence: 75%
“…PTHrP raises calcium levels in serum and is the principal agent of hypercalcemia of malignancy (18). PTHrP also promotes the metastasis of prostate cancer cells to bone (19,20). Thus, we suggest that the production of PTHrP by local prostate tumors is a plausible mechanism that could underlie the association between higher serum calcium and decreased prostate cancer survival.…”
Section: Discussionmentioning
confidence: 78%